Civil law problems and morbidity. Issue 7 (11th June 2004) - Pleasence, P; Balmer, N J; Buck, A; O'Grady, A; Genn, H
Abstract : Study objective: In the United Kingdom, recognition of the links between social and health problems has led to government initiatives such as health action zones. The principles of civil law apply to many types of social problem, and the civil justice system provides one means through which they can be tackled. However, little research has been undertaken into the particular links between problems to which civil legal principles and processes can be applied and morbidity. This study examines these links, and the role of legal advice and services in preventing ill health. Design: This study examined survey respondents' self reports of longstanding illness/disability and experience of 18 problems to which legal principles can be applied. Setting: A random national survey conducted across England and Wales. Participants: 5611 adults drawn from 3348 residential households. Main results: Significant associations were found between illness/disability and 13 of the problem types. Moreover, experience of greater numbers of problems increased the likelihood of reported illness/disability. In attempting to resolve problems respondents' health also frequently suffered. Conclusions: This study highlights the contribution that public legal education and legal advice can make to the promotion of public health, and the importance of further integration of health and civil justice initiatives through health action zones, community legal service partnerships, etc, to further this end.